Response of summer irrigated black gram (Vigna mungo L.) to planting method and weed management methods under western agro-climatic zones of Tamil Nadu - Senthamizhselvan, S; Anitta, FS; Raju, M; Babu, RPV; Mohankumar, AP (Plant Science Today, 2025)
To assess the effect of sowing methods and weed management on summer irrigated black gram yield, a field experiment was conducted during the summer season of 2024 in the Department of Pulses at Tamil Nadu Agricultural University, Coimbatore. The treatments were employed in the Split plot design and replicated thrice. The sowing methods and weed management treatments were allotted in the main and subplots, respectively. The findings showed that, among the sowing methods, furrow-irrigated raised beds recorded a lower weed density and concerning weed management, the pre-emergence (PE) application of Pendimethalin 30 % + Imazethapyr 2 % EC (ready mix) and weeding with power-operated weeder at 20 DAS resulted in lesser weeds which leads to higher weed control efficiency (79.88 %) and higher seed yield in both furrow-irrigated raised beds and pre-emergence (PE) application of Pendimethalin 30 % + Imazethapyr 2 % EC (ready mix) and weeding with power-operated weeder at 20 DAS.